2020
DOI: 10.4236/ce.2020.1111171
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence during the Implementation of an Educational Chatbot with the Electroencephalogram Metric

Abstract: A student's attention status during a digital conversation can differ when talking to an intelligent agent, that is, a chatterbot interactive. There is evidence that brain waves have different oscillations during the study. A virtual platform with an artificial intelligence chatterbot was explored in this study. During the study, participants were asked to use the Neurosky Mindwave sensor to assess their attention levels in real time. Statistical analyses of the results revealed significant effects on the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…NeuroSky MindWave was used to collect brain wave data (Bos et al, 2020; Galíndez‐Floréz et al, 2020). This headphone‐type EEG device has a sensory point that touches the forehead and another that is clamped to the earlobe (Over‐Paradigm, 2021), as shown in Figure 3.…”
Section: Research Design and Implementationmentioning
confidence: 99%
“…NeuroSky MindWave was used to collect brain wave data (Bos et al, 2020; Galíndez‐Floréz et al, 2020). This headphone‐type EEG device has a sensory point that touches the forehead and another that is clamped to the earlobe (Over‐Paradigm, 2021), as shown in Figure 3.…”
Section: Research Design and Implementationmentioning
confidence: 99%
“…While acknowledging the inherent complexity of brain states and wave activity, delving into the extent to which distinct brain wave frequencies exert influence during a chat session presents an intriguing avenue for investigating the emotional states of the user. In a study by Bos et al [ 22 ], the authors explored capturing vigilance and states of emotion with EEG in usability testing of chatbot technology. The study findings revealed that EEG effectively captured the facets of user experience and conversation that piqued interest.…”
Section: Introductionmentioning
confidence: 99%